Evaluation of the Patients, Doctors and Nurses View Points about Patient Bill of Rights in Rasht Public Hospitals - Zahra Bostani Khalesi; Shademan Masole; Mahmoud Abedinzade (Journal of Advanced Biomedical Sciences, 2012)
Background & Objective: With the aim to clarify the rights of the patients on the basis of medical ethic norms, Patient Bill of Rights in five categories was developed in Iran for the first time, during 2002. The main objective of this study was to determine the views of patients, physicians and nurses about this aspect of medical ethics and its necessary to comply in Rasht public hospitals. Materials ;Methods: In this cross-sectional study the data were collected by filling a reliable and validated questionnaire consisting of demographic part and 25 specific questions about the rights of patients, these questions were answered By 185 patients, 22 nurses and 14 doctors. Each of the criteria necessary to use was measured by the Likert scale from zero (completely disagree) to five (fully agree). SPSS software 16 and one way ANOVA tests were used for data analysis. Result: The results showed that all groups were agreeing with the necessity to have a bill and consider the patient's rights during treatment (P<0.05). But the most controversial point were related to the rights of patient to have access to their information and the right to choose and decide (P<0.05). However, 68.2 percent of physicians, 80.05 percent of nurses, and 93 percent of patients were agreed with the Bill of Rights. Conclusion: Although all the groups were agreed with the patient's Bill of rights (P<0.05), It seems it is necessary to reconsider the issue of providing the necessary information to the patient and give attention to their choices and decisions by the medical health service providers.